Enteropathogens: Tuning Their Gene Expression for Hassle-Free Survival - Chatterjee, Ritika; Shreenivas, Meghanashree M.; Sunil, Rohith; Chakravortty, Dipshikha (Frontiers in Microbiology, 2019)
Enteropathogenic bacteria have been the cause of the majority of foodborne illnesses. Much of the research has been focused on elucidating the mechanisms by which these pathogens evade the host immune system. One of the ways in which they achieve the successful establishment of a niche in the gut microenvironment and survive is by a chain of elegantly regulated gene expression patterns. Studies have shown that this process is very elaborate and is also regulated by several factors. Pathogens like, enteropathogenic Escherichia coli (EPEC), Salmonella Typhimurium, Shigella flexneri, Yersinia sp. have been seen to employ various regulated gene expression strategies. These include toxin-antitoxin systems, quorum sensing systems, expression controlled by nucleoid-associated proteins (NAPs), several regulons and operons specific to these pathogens. In the following review, we have tried to discuss the common gene regulatory systems of enteropathogenic bacteria as well as pathogen-specific regulatory mechanisms.